2018
DOI: 10.1080/15332640.2018.1433094
|View full text |Cite
|
Sign up to set email alerts
|

U.S. adolescent alcohol use by race/ethnicity: Consumption and perceived need to reduce/stop use

Abstract: Understanding racial/ethnic drinking patterns and service provision preferences is critical for deciding how best to use limited alcohol prevention, intervention, and treatment resources. We used nationally representative data from 150,727 U.S. high school seniors from 2005 to 2016 to examine differences in a range of alcohol use behaviors and the felt need to reduce or stop alcohol use based on detailed racial/ethnic categories, both before and after controlling for key risk/protective factors. Native student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 54 publications
6
19
0
1
Order By: Relevance
“…Spanish students reported higher alcohol consumption than non-Spanish students. This finding is similar to a study carried out in the United States [52], which showed that US-born adolescents reported higher use. It seems that living in one's birth country is related to alcohol use in the Spanish context.…”
Section: Discussionsupporting
confidence: 91%
“…Spanish students reported higher alcohol consumption than non-Spanish students. This finding is similar to a study carried out in the United States [52], which showed that US-born adolescents reported higher use. It seems that living in one's birth country is related to alcohol use in the Spanish context.…”
Section: Discussionsupporting
confidence: 91%
“…Spanish students reported higher alcohol consumption than non-Spanish students. This finding is similar to a study carried out in the United States [54], which showed that US-born adolescents reported higher use. It seems that living in one's birth country is related to alcohol use in the Spanish context.…”
Section: Discussionsupporting
confidence: 91%
“…1 Similar to national data demonstrating less alcohol use and lower rates of alcohol use disorder among Asian Americans (Terry-McElrath and Patrick, 2018;Vaeth et al, 2017), in the current dataset Asian Americans averaged fewer typical drinks and drank and binge drank less frequently than non-Asian-American students. Among drinkers, there were no differences between these groups at semester 1, but Asian American drinkers reported lower alcohol use (across all measures) than non-Asian American drinkers in the final semester survey.…”
Section: Resultssupporting
confidence: 70%